Adult Pleomorphic Rhabdomyosarcomas: Assessing Outcomes Associated with Radiotherapy and Chemotherapy Use in the National Cancer Database. (16th March 2021) - Reddy, Vishruth K.; Jain, Varsha; Wilson II, Robert J.; Hartner, Lee P.; Diamond, Mark; Sebro, Ronnie A.; Weber, Kristy L.; Maki, Robert G.; Shabason, Jacob E.
Abstract : Purpose . Practice patterns for treatment of localized adult pleomorphic rhabdomyosarcoma (PRMS) remain quite variable given its rarity. Current national guidelines recommend management similar to that of other high-grade soft tissue sarcomas (STS), which include surgery with perioperative radiation (RT) with or without chemotherapy. Using the National Cancer Database (NCDB), we assessed practice patterns and overall outcomes of patients with localized PRMS. Patients and Methods . Patients with stage II/III PRMS treated with surgical resection from 2004 to 2015 were identified from the NCDB. Predictors of RT and chemotherapy use were assessed using multivariable logistic regression analysis. The association of radiation and chemotherapy status on overall survival was assessed using Kaplan–Meier and Cox proportional hazards analyses. Results . Of 243 total patients, RT and chemotherapy were not uniformly utilized, with 44% receiving chemotherapy and in those who did not undergo amputation 62% receiving RT. In those who did not undergo amputation, RT was associated with improved survival on both univariate (HR: 0.49, 95% CI 0.32–0.73, P < 0.001 ) and multivariate analysis (HR: 0.40, 95% CI 0.26–0.62, P < 0.001 ), corresponding to greater 5-year overall survival (59% vs. 38%, P < 0.001 ). Chemotherapy was associated with a higher rate of 5-year overall survival (63% vs. 39%, P < 0.001 ). However, the survival benefit of chemotherapy did not reach statistical significance on multivariate analysis (HR: 0.65, 95% CI 0.41–1.03, P = 0.064 ). Notable predictors of omission of RT included female gender (OR: 0.40, 95% CI 0.22–0.74, P < 0.01 ) and age ≥ 70 (OR: 0.55, 95% CI 0.30–1.00, P = 0.05 ). Correspondingly, factors associated with omission of chemotherapy included age ≥70 (OR: 0.17, 95% CI 0.08–0.39, P < 0.001 ). Conclusions . A significant proportion of patients with localized adult PRMS are not receiving RT. Likewise, use of chemotherapy was heterogeneous. Our findings note potential benefits and underutilization of RT, for which further investigation is warranted.